Model Perubahan Komposisi Gas CO2 dan O2 Buah Salak Pondoh (Salacca edulis, Reinw) pada Pengemasan Plastik Polietilen dalam Atmosfir Termodifikasi - Amin Rejo; Budi Raharjo; Tranggono Tranggono (agriTECH, 2001)
Storing fruit with high concentration of carbondioxyde and low concentration of oxygen could be utilized to retard respiration rate, moisture loss, fruit repening, enzyme activities and microbial growth. Mathematical models were developed for respiration of salak pondoh (Salacca edulis Review., cultivar pondoh), permeability of polyethylene plastic packaging and gas exchange in packaging. The apparatus used in the experiment was a packaging tube covered with 0.08 mm thick polyethylene tube was flowed with modified atmosphere. Spectrophotometry and gas chromatography were used to assay the gas, and data obtained from model and from experiment were compared. The results showed that the models can predict the respiration rate RCO2 = 11.75 CCO2-0.08 CO21.47 e-0.22 (t) and RCO2 = 16.946 CCO2-0.485 O20.264 e-0.063 (t) , permeability of polyethylene plastic packaging DCO2 = 0.623 e-9.074 (67.13/R 1/T) and DO2 = 0.077 e-21.144 (75.79/R 1/T) and gas exchange in packaging (Cm+1 = Cm + ΔCn).